The very possibility of contemplation: The dialectics of intellect and will in Schopenhauer's aesthetics. - Sattar, Alexander (Southern Journal of Philosophy, 2025)
In this article, I explore how Schopenhauer's theory of aesthetic experience—independently of his theory of arts—accommodates the possibility of contemplation. The standard reading of his aesthetics is that contemplation becomes possible because of a certain "surplus" of intellect and facilitating external occasions. I argue, however, that the "essential imperfections" of intellect and Schopenhauer's overall metaphysics are inconsistent with the very idea of will‐less cognition and, hence, of a free intellect. An alternative explanation of contemplation better fits with Schopenhauer's philosophy overall by stating that it is driven by the will itself. I analyze two approaches to elaborating such a theory. First, the "metaphysical" account, according to which the will as thing‐in‐itself brings forth the (surplus of) intellect needed for contemplation as a means of self‐cognition. Second, the "physiological" account, which presupposes a quasi‐evolutionary process that has aesthetic cognition as a byproduct of intellect. The two accounts complement each other and in tandem better explain the possibility of contemplation than postulating a will‐less intellect.